2010
DOI: 10.1111/j.1740-0929.2010.00768.x
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic detection of IgY‐Fc binding signal in the inner layers of ovarian follicular tissue in quail

Abstract: In avian species, it has been assumed that an Fc receptor in the ovarian follicles mediates immunoglobulin Y (IgY) transport into the yolk. However, no such receptor responsible for IgY has been identified to date. To examine potential IgY binding activity in the entire ovarian follicle, whole-mount sections of quail ovarian follicle were incubated with the Fc fragment of chicken IgY (cIgY). Whole-mount frozen sections of the second largest ovarian follicle were prepared, and then the sections were incubated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Nevertheless, the Y363A mutant had infiltrated into the granulosa cell layer, suggesting that a major hurdle disturbing the infiltration of the Y363A mutant lies on the inside of the granulosa cell layer such as the perivitelline layer and/or oocyte plasma membrane (Murai et al, 2013). Our previous study using whole-mount sections of quail ovarian follicles also showed that potential IgY binding substances interacting with the Fc domain are present around the perivitelline layer (Kitaguchi et al, 2010). These results strongly support the classical idea that a receptor involved in maternal IgY transfer exists in the perivitelline layer and/or oocyte plasma membrane.…”
Section: Relevance Of Igy-fc Receptor On Ig Uptake Into Egg Yolksmentioning
confidence: 94%
“…Nevertheless, the Y363A mutant had infiltrated into the granulosa cell layer, suggesting that a major hurdle disturbing the infiltration of the Y363A mutant lies on the inside of the granulosa cell layer such as the perivitelline layer and/or oocyte plasma membrane (Murai et al, 2013). Our previous study using whole-mount sections of quail ovarian follicles also showed that potential IgY binding substances interacting with the Fc domain are present around the perivitelline layer (Kitaguchi et al, 2010). These results strongly support the classical idea that a receptor involved in maternal IgY transfer exists in the perivitelline layer and/or oocyte plasma membrane.…”
Section: Relevance Of Igy-fc Receptor On Ig Uptake Into Egg Yolksmentioning
confidence: 94%
“…functioning in immunomodulation and IgY transfer have already been identified in the chicken (West et al, 2004;Viertlboeck et al, 2005;Viertlboeck et al, 2009). However, the expressions of these receptor genes are undetectable, at least in the granulosa cell layer of ovarian follicles, which generally synthesizes and provides endocytotic receptors for the development of oocytes (Kitaguchi et al, 2010;unpublished data). To identify a true receptor transferring IgY into egg yolks, it will be necessary to isolate the IgY-Fc receptor from ovarian follicular tissues, and to perform a thorough receptor binding assay with IgY mutants both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 95%
“…Our previous study showed that an Fc portion mainly containing C 3 and C 4 domains is essential for effective IgY transport into egg yolks, since intravenouslyinjected IgY-Fc fragments were effectively transported into egg yolks, whereas Fab and F(ab')2 fragments were poorly transported into egg yolks (Kitaguchi et al, 2008). It has been assumed that this selective IgY transport is mediated by an IgY-Fc receptor located on the perivitelline and/or oocyte plasma membrane (Morrison et al, 2001;Bae et al, 2010b;Kitaguchi et al, 2010), but such a receptor has not been identified yet, and the molecular basis of this selective IgY transport remains unclear.…”
Section: Introductionmentioning
confidence: 96%